2021
DOI: 10.1371/journal.pone.0250512
|View full text |Cite
|
Sign up to set email alerts
|

Rice bran oil emulgel as a pork back fat alternate for semi-dried fish sausage

Abstract: The objective of this study was to investigate the effects of rice bran oil emulsion filled gels (EG) substitution for pork back fat on the characteristics of Chinese style semi-dried tilapia sausage (CFS). EG prepared using different gelling agents and processing conditions were used as pork back fat alternate in the CFS. From the results, physical, chemical and microstructural qualities of CFS were governed by the type of EG incorporated. Regarding the overall quality, CFS formulated with carrageenan-EG was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…On the other hand, hardness, adhesiveness, and chewiness were significantly different among sausages with different content of fat. Previous studies found a high correlation between fat level and hardness, and products obtained with low‐fat formulation were softer than high fat formulation while the protein content were held constant (Chaijan et al., 2021; Poyato et al., 2014). In the present study, hardness of sausage H was significantly higher than sausage L. This was probably because the addition of water exists between the myofibrils as free water.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, hardness, adhesiveness, and chewiness were significantly different among sausages with different content of fat. Previous studies found a high correlation between fat level and hardness, and products obtained with low‐fat formulation were softer than high fat formulation while the protein content were held constant (Chaijan et al., 2021; Poyato et al., 2014). In the present study, hardness of sausage H was significantly higher than sausage L. This was probably because the addition of water exists between the myofibrils as free water.…”
Section: Resultsmentioning
confidence: 97%
“…Numerous recent studies have reported the development of emulsion gels and the properties of their dispersed and continuous phases. These studies include an investigation of sausages prepared by substituting pork back fat with emulsion gels [5] and the production of a low-fat mayonnaise using emulsion gels [6]. However, research efforts have tended to focus primarily on O/W emulsion gels, whereas waterin-oil (W/O) emulsion gels have received comparatively limited attention [7,8].…”
Section: Introductionmentioning
confidence: 99%